STUDI POLA INTERAKSI PERILAKU JANGKRIK (Gryllus bimaculatus ) JANTAN DAN BETINA - Anwari Adi Nugroho; Namira Hanin Sal Sabilla; Dwi Setyaningrum; Fikih Putri Prastin; Talila Rima Dani (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
The purpose of this study was to observe the behavior of male and female cricket (Gryllus bimaculatus) interactions. The objects of this study were five male crickets and one female cricket that had been isolated for twenty-four hours. This research is an exploratory descriptive study observing all male and female cricket (gryllus bimaculatus) behaviors. The research method used is ad libitum which is observing all visible activities, both social behavior and daily behavior of male and female crickets. Retrieval of data using direct observation, recording sounds and then recorded in the observation sheet, observation notes, and documentation tools. The data that has been collected is then analyzed using descriptive analysis techniques that describe the behaviors that arise during observation. The results showed that the behavior that is often performed by crickets is sounding, eating, climbing, mating and attacking other crickets. Crickets perform sounding behavior to attract the attention of female crickets, show their existence and to defend their territory and food sources. crickets also often climb, to escape from the container because crickets want to live freely. Crickets perform eating behavior to maintain life and will show aggressive behavior when fighting over food and when maintaining their partners. Female crickets will mating if captivated by male crickets.